Mesenchymal Stem Cells Attenuate the Adverse Effects of Immunosuppressive Drugs on Distinct T Cell Subopulations - Hajkova, Michaela; Hermankova, Barbora; Javorkova, Eliska; Bohacova, Pavla; Zajicova, Alena; Holan, Vladimir; Krulova, Magdalena (Stem cell reviews, 2017)
Immunosuppressive drugs are widely used to treat undesirable immune reaction, however their clinical use is often limited by harmful side effects. The combined application of immunosuppressive agents with mesenchymal stem cells (MSCs) offers a promising alternative approach that enables the reduction of immunosuppressive agent doses and simultaneously maintains or improves the outcome of therapy. The present study aimed to determinate the effects of immunosuppressants on individual T cell subpopulations and to investigate the efficacy of MSC-based treatment combined with immunosuppressive drugs. We tested the effect of five widely used immunosuppressants with different action mechanisms: cyclosporine A, mycophenolate mofetil, rapamycin, and two glucocorticoids - prednisone and dexamethasone in combination with MSCs on mouse CD4+ and CD8+ lymphocyte viability and activation, Th17 (RORγt+), Th1 (T-bet+), Th2 (GATA-3+) and Treg (Foxp3+) cell proportion and on the production of corresponding key cytokines (IL-17, IFNγ, IL-4 and IL-10). We showed that MSCs modulate the actions of immunosuppressants and in combination with immunosuppressive drugs display distinct effect on cell activation and balance among different T lymphocytes subpopulations and exert a suppressive effect on proinflammatory T cell subsets while promoting the functions of anti-inflammatory Treg lymphocytes. The results indicated that MSC-based therapy could be a powerful strategy to attenuate the negative effects of immunosuppressive drugs on the immune system.
Keywords: Cell Survival; dexamethason; kokultivační techniky; Glucocorticoids; Mesenchymal Stem Cell Transplantation; cytokiny; Female; Prednisone; Sirolimus; Mycophenolic Acid; myši inbrední BALB C; sirolimus; zvířata; proliferace buněk; Cells, Cultured; Lymphocyte Activation; imunosupresiva; Mice, Inbred BALB C; T-Lymphocyte Subsets; Coculture Techniques; Immunosuppressive Agents; prednison; cyklosporin; aktivace lymfocytů; ženské pohlaví; transplantace mezenchymálních kmenových buněk; Mesenchymal Stem Cells; Flow Cytometry; mezenchymální kmenové buňky; kultivované buňky; Cell Proliferation; Dexamethasone; glukokortikoidy; Cytokines; kyselina mykofenolová; průtoková cytometrie; Cyclosporine; Animals; viabilita buněk; T-lymfocyty - podskupiny